Jie Du Tong Ye San Prevents N-Nitrosomethylbenzylamine-Induced Esophageal Carcinogenesis via Inhibition of Inflammation and Proliferation. (20th May 2019) - Zhao, Simin; Jiang, Yanan; Tian, Tongde; Zhao, Jimin; Xie, Yifei; Chen, Xinhuan; Lu, Jing; Yang, Feng; Li, Honglin; Liu, Kangdong; Dong, Ziming
Abstract : Jie du tong ye san (JDTYS), a traditional Chinese herbal formula, has been used for cancer adjuvant therapy in clinical use and has been shown to be effective in cancer patients. However, the mechanism of JDTYS is still unclear. Therefore, the aim of the present study is to investigate the chemopreventive effects of JDTYS for esophageal squamous cell carcinoma (ESCC) and to clarify the potential mechanism. N-nitrosomethylbenzylamine (NMBA)-induced rat esophageal carcinogenesis was used to evaluate the effect of JDTYS in vivo . Rats were treated with NMBA 3 times per week, for a total of 5 weeks. Rats in the treated groups were given JDTYS for 35 weeks. When rats were euthanized, esophageal tissue and blood were collected to evaluate the effects of JDTYS. The pathological grading of the rat esophageal preneoplastic lesions was classified and statistically analyzed. The protein levels of c-Jun and Ki67 were determined by immunohistochemistry. In addition, inflammation markers nuclear factor kappa B (NF- κ B), cyclooxygenase-2 (COX-2), and the cluster of differentiation molecule 11B (CD11B) were also determined by immunohistochemistry. Moreover, the expression of COX-2 and Pentraxin 3 (PTX3) in rat serum was determined by enzyme-linked immunosorbent assay (ELISA). JDTYS could inhibit the formation of NMBA-induced esophageal preneoplastic lesions. JDTYS could downregulate the expression of proliferation related proteins Ki67 and c-Jun. Moreover, inflammation related proteins NF- κ B, COX-2, and CD11B were inhibited and PTX3 was increased by JDTYS. In all, JDTYS is a promising chemopreventive formula against esophageal carcinogenesis by regulating inflammation and inhibiting cell proliferation.